2015
DOI: 10.1002/chem.201405658
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Live Cell Viscosity with an Aggregation‐Induced Emission Fluorogen by Means of Two‐Photon Fluorescence Lifetime Imaging

Abstract: Intracellular viscosity is a crucial parameter that indicates the functioning of cells. In this work, we demonstrate the utility of TPE-Cy, a cell-permeable dye with aggregation-induced emission (AIE) property, in mapping the viscosity inside live cells. Owing to the AIE characteristics, both the fluorescence intensity and lifetime of this dye are increased along with an increase in viscosity. Fluorescence lifetime imaging of live cells stained with TPE-Cy reveals that the lifetime in lipid droplets is much sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 42 publications
0
62
0
Order By: Relevance
“…TPE‐Cy, which has been used as a pH and viscosity sensor as described in Sections and , can also be used to image and locate LDs . As shown in Figure g, fluorescence imaging revealed that almost all membrane‐bound organelles were lit up by TPE‐Cy, and the intense blue spots were mainly LDs.…”
Section: Lighting Up Subcellular Organellesmentioning
confidence: 99%
See 1 more Smart Citation
“…TPE‐Cy, which has been used as a pH and viscosity sensor as described in Sections and , can also be used to image and locate LDs . As shown in Figure g, fluorescence imaging revealed that almost all membrane‐bound organelles were lit up by TPE‐Cy, and the intense blue spots were mainly LDs.…”
Section: Lighting Up Subcellular Organellesmentioning
confidence: 99%
“…As described in the pH sensing part, TPE‐Cy is a cell‐permeable AIE molecule that can detect the full‐range intracellular pH values. The same dye was tested to see if it can be used as a viscosity sensor . The authors collected the lifetime information of the dye following two‐photon (TP) excitation at 600 nm and found that the dye also succeeded in sensing the intracellular viscosity.…”
Section: Lighting Up Intracellular Microenvironmentsmentioning
confidence: 99%
“…In this work, we utilized BODIPY‐C 10 17, 18 (Figure 1), a fluorophore that belongs to a group of dyes termed ‘molecular rotors’ that have viscosity‐dependent fluorescence quantum yields, lifetimes,19, 20 and depolarization 21, 22. When combined with fluorescence lifetime imaging microscopy (FLIM), molecular rotors can be used to obtain spatially resolved viscosity maps of microscopic objects,17, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40 as well as to observe dynamic change in viscosity during relevant processes of interest 37, 39, 41, 42. Thus, we aimed to use BODIPY‐C 10 , which is known to completely embed into the fluid‐phase lipid bilayers40 to directly examine how photooxidation during PDT affects viscoelastic properties of model lipid membranes, with spatial‐ and time‐resolution.…”
Section: Introductionmentioning
confidence: 99%
“…1,[5][6][7] The Brownian motion of the probe could be tracked by using video-based methods or by the analysis of its emission, in the case of luminescent probes. 5,[8][9][10] On the other hand, active techniques exert a force over the cell to test its response to the applied stimulus. 11,12 The action could be performed directly over the cell or by using a probe (usually polystyrene or silica beads).…”
Section: Introductionmentioning
confidence: 99%